2015
DOI: 10.1158/1538-7445.am2015-4721
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4721: Epithelial to mesenchymal transition is not required for breast to lung metastasis but contributes to chemoresistance

Abstract: The role of epithelial to mesenchymal transition (EMT) in metastasis is a longstanding source of controversy, largely due to an inability to monitor transient and reversible EMT phenotypes in vivo. We have established a novel and unique EMT lineage tracing system in spontaneous breast to lung metastasis models. In these models, mesenchymal-specific Cre-mediated recombination initiates permanent switch of fluorescent markers in tumor cells undergoing EMT. This allows us to track EMT tumor cells in the primary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Indeed, the correlation between EMT, increased ZEB1/2dependent expression of MDR1 and ABCG2, and resistance to platinum-based drugs was confirmed by the whole transcriptome profiling of ovarian and lung cancer tissues (Zhou Y. et al, 2017;Wu et al, 2019a). Finally, several recent studies demonstrated decreased sensitivity to chemotherapy of primary and metastatic tumor cells in an EMT-dependent manner in both lung and pancreatic cancers (Fischer et al, 2015;Zheng et al, 2015). These reports provide convincing data linking EMT to chemoresistance.…”
Section: Interplay Between Micrornas Zeb1 and Dna Damage Responsementioning
confidence: 62%
See 2 more Smart Citations
“…Indeed, the correlation between EMT, increased ZEB1/2dependent expression of MDR1 and ABCG2, and resistance to platinum-based drugs was confirmed by the whole transcriptome profiling of ovarian and lung cancer tissues (Zhou Y. et al, 2017;Wu et al, 2019a). Finally, several recent studies demonstrated decreased sensitivity to chemotherapy of primary and metastatic tumor cells in an EMT-dependent manner in both lung and pancreatic cancers (Fischer et al, 2015;Zheng et al, 2015). These reports provide convincing data linking EMT to chemoresistance.…”
Section: Interplay Between Micrornas Zeb1 and Dna Damage Responsementioning
confidence: 62%
“…Previous studies demonstrated that highly proliferative non-EMT breast cancer cells were sensitive to chemotherapy, while the emergence of recurrent EMT-derived metastases was associated with resistance to cyclophosphamide in vivo (Fischer et al, 2015). Also, miR-200 overexpression results in the switch toward cyclophosphamide sensitivity (Fischer et al, 2015). These results indicate potential relevance of EMT in the chemoresistance, as the main target of miR-200 is ZEB1, a crucial regulator of EMT that is capable of reversing the whole machinery (Bracken et al, 2014).…”
Section: Interplay Between Micrornas Zeb1 and Dna Damage Responsementioning
confidence: 92%
See 1 more Smart Citation
“…options and therapeutic outcome. EMT is linked not only to increased metastasis (Yang et al, 2004;Mani et al, 2007;Ocana et al, 2012;Stankic et al, 2013) but also to chemoresistance (Singh and Settleman, 2010;Haslehurst et al, 2012;Ren et al, 2013;Fischer et al, 2015;Zheng et al, 2015;Li H. et al, 2019;Li N. et al, 2019). EMT in cancer is associated with the acquisition of a more stem-cell-like character.…”
Section: The Ecm Regulates Emt and Metastasismentioning
confidence: 99%
“…EMT in cancer is associated with the acquisition of a more stem-cell-like character. Accordingly, Fisher et al found that the cyclophosphamide resistance of tumor cells that acquired a mesenchymal character could be attributed to reduced proliferation and increased expression of drug efflux pumps (ABCC1, ABCB1) and of enzymes involved in drug metabolism, like cytochrome p450s (Fischer et al, 2015), traits that are characteristic for stem and progenitor populations.…”
Section: The Ecm Regulates Emt and Metastasismentioning
confidence: 99%